Characterisation and modelling the mechanics of cellulose nanofibril added polyethersulfone ultrafiltration membranes - Acarer, Seren; Pir, Inci; Tufekci, Mertol; Erkoc, Tugba; Oztekin, Vehbi; Durak, Sevgi Gunes; Ozcoban, Mehmet Surku; Demirkol, Guler Turkoglu; Alhammod, Moayyad; Cavus, Selva; Tufekci, Nese (CELL PRESS, 2023)
The performance of the membranes can be improved by adding the appropriate amount of nanomaterials to the polymeric membranes that can be used for water/wastewater treatment. In this study, the effects of polyvinylpyrrolidone (PVP), the impact of different amounts (0.5% and 1% wt.) of cellulose nanofibril (CNF), and the combined effects of PVP-CNF on the properties/ performance of the polyethersulfone-based (PES-based) membrane are investigated. All PES-based ultrafiltration (UF) membranes are manufactured employing the phase inversion method and characterised via Fourier transform infrared (FTIR) spectroscopy, scanning electron micro-scopy (SEM), and the relevant techniques to determine the properties, including porosity, mean pore size, contact angle, water content, and pure water flux tests. Furthermore, the thermal properties of the prepared membranes are investigated using thermal gravimetric analysis (TGA) and differential thermal analysis (DTA) techniques. Experimental and numerical methods are applied for the mechanical characterisation of prepared membranes. For the experimental pro-cess, tensile tests under dry and wet conditions are conducted. The finite element (FE) method and Mori-Tanaka mean-field homogenisation are used as numerical methods to provide more detailed knowledge of membrane mechanics.
Keywords: Nanocomposite membrane; Membrane characterisation; Cellulose nanofibril; Mechanical modelling; ANTIFOULING PERFORMANCE; COMPOSITES; GO; Science & Technology - Other Topics